2019
DOI: 10.1093/ofid/ofz070
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Hepatitis C Treatment Failure After Using Direct-Acting Antivirals in People Living With Human Immunodeficiency Virus

Abstract: Background Little is known about the influence of ongoing barriers to care in the persistence of hepatitis C virus (HCV) viremia after treatment with direct-acting antivirals (DAAs) among people living with human immunodeficiency virus (PLWH). Methods We conducted a retrospective cohort analysis of PLWH treated through the standard of care in 3 Western countries, to investigate the predictors of HCV treatment failure (clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 31 publications
3
23
2
Order By: Relevance
“…Other studies have found alcohol use, illicit drug use, and mental illness to be associated with HCV treatment non-completion; however these findings were not replicated in our study [ 21 , 24 , 40 ]. The unique structure of our program, which operates with an emphasis on educating and supporting our patients with alcohol and substance use disorders based on structured psychosocial assessment, may play a role in the lack of association of these exposures with treatment non-adherence.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Other studies have found alcohol use, illicit drug use, and mental illness to be associated with HCV treatment non-completion; however these findings were not replicated in our study [ 21 , 24 , 40 ]. The unique structure of our program, which operates with an emphasis on educating and supporting our patients with alcohol and substance use disorders based on structured psychosocial assessment, may play a role in the lack of association of these exposures with treatment non-adherence.…”
Section: Discussioncontrasting
confidence: 99%
“…In the wake of treatment innovations, such as DAAs and improved access to community-based care for SUD and HCV treatment in non-specialized settings, there has been significant progress and evidence of comparable cure rates being achieved in people who inject drugs as compared to other patient groups in clinical trials [18][19][20][21]. Despite these advances, there remains evidence of suboptimal treatment adherence and clinical outcomes among some groups of HCV patients, including persons with active IDU or HIV co-infection, as a complex array of clinical and psychosocial barriers continues to deter treatment success in real world cohorts of these historically vulnerable populations [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The results of our study show that these follow up losses in the group of psychiatric vs nonpsychiatric patients must be attributed to MDSDU‐patients and not to patients with other psychiatric disorders. These results reinforce the importance of care in integrated multidisciplinary health systems for the treatment of psychiatric patients, as is currently recommended, since they promote clinical adherence and improve the likelihood of achieving SVR in this subgroup of patients 47‐49 . The results of our study are in line with those reported in similar studies, in which the SVR12 reached with DAAs in patients with psychosocial comorbid conditions, substance use, mental health disorders, psychiatric disease or illicit drug use, was found among the 90%‐96% 50‐54 .…”
Section: Discussionsupporting
confidence: 91%
“…These results reinforce the importance of care in integrated multidisciplinary health systems for the treatment of psychiatric patients, as is currently recommended, since they promote clinical adherence and improve the likelihood of achieving SVR in this subgroup of patients. [47][48][49] The results of our study are in line with those reported in similar studies, in which the SVR12 reached with DAAs in patients with psychosocial comorbid conditions, substance use, mental health disorders, psychiatric disease or illicit drug use, was found among the 90%-96%. [50][51][52][53][54] Of particular interest are the results observed by A high and very similar global therapeutic safety has been observed in the group of psychiatric patients vs nonpsychiatric patients, with very similar incidence rates of mild, moderate, or severe adverse effects reported by the patients, as well as visits to the emergency room or treatment withdrawals secondary to the development of serious adverse effects.…”
Section: The Importance Of Adherence To Antiviral Treatment Based Onsupporting
confidence: 92%
“…This observation has been acknowledged by international guidelines [131]. However, consideration of this sub-population is still warranted given evidence suggesting that persons with HIVÀHCV coinfection are at risk of HCV treatment failure for factors such as ongoing illicit drug use and mental illness [132]. Analyses of harms suggest consistency across treatments for the very low proportions of persons with DAEs, SAEs, or all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%